2012
DOI: 10.1007/s12519-012-0335-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase 99mTc-dimercaptosuccinic acid scan in infants with first episode of febrile urinary tract infection

Abstract: Parenchymal damage found in a minority of infants with febrile UTI presented promptly to the hospital. Acute phase DMSA scan should be carried out only in selected patients. An abnormal acute DMSA scan is a moderate predictor for dilated VUR and its ability to exclude VUR is restricted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
5
15
0
1
Order By: Relevance
“…15,16 The rate of VUR in patients with abnormal DMSA was 41.3% (164/ 397), which was also in agreement with previous data. 17 However, we noticed a relatively high percentage of dilating VUR (28.9% of patients; 187/1046 = 17.8% of renal units), which was higher than that reported in some studies, 5,18 but was close to the proportion found in other reports.…”
Section: Discussionsupporting
confidence: 91%
“…15,16 The rate of VUR in patients with abnormal DMSA was 41.3% (164/ 397), which was also in agreement with previous data. 17 However, we noticed a relatively high percentage of dilating VUR (28.9% of patients; 187/1046 = 17.8% of renal units), which was higher than that reported in some studies, 5,18 but was close to the proportion found in other reports.…”
Section: Discussionsupporting
confidence: 91%
“…Our study revealed that most of the DMSA scan results were negative for children who had only one episode of uncomplicated UTI (93.7%). Similar results have been obtained by studies done in other countries [5][6][7]. In conclusion, the conventional practice of recommending DMSA scans following UTI should be modified with an evidence-based protocol.…”
Section: Brief Reportsupporting
confidence: 86%
“…Expected prevalence of abnormalities on DMSA scans was taken as 15% according to the findings of Printza and others [5]. Significance level (alpha error) was taken as 95% and the level of precision as 5%.…”
Section: No 2 June 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…Acute-phase DMSA scan shows renal changes in 16.3% of infants experiencing their first febrile UTI (3). Clinical studies have demonstrated that dimercaptosuccinic acid (DMSA) scan is significantly more sensitive than either intravenous pyelography (IVP) or ultrasonography (US) in the diagnosis of acute pyelonephritis (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%